EDUCATING FOR PROFESSIONALISM: A NEW MILITARY FOR A NEW SOUTH AFRICA - Esterhuyse, Abel (Scientia Militaria - South African Journal of Military Studies, 2011)
This article explores the role of education in professionalising the South African National Defence Force (SANDF) since 1994. The central thesis is that military education, training and development played a major role in bringing the pre- 1994 belligerent forces in South Africa together and blending them into a single, coherent, bureaucratised defence force. There is, however, reason for serious concern. The article first outlines the specific need for education in the SANDF since 1994. The second part provides an overview of the educational institutions in the SANDF, their programmes and the nature of education, training and development that are provided. The final section discusses the most salient factors that have influenced education in the SANDF over the last decade. Specific emphasis is placed on the lack of suitably qualified academic staff, the difficulty of educating soldiers in a second or third language, the lack of research and the presence of an institutional climate of anti-intellectualism.